Activity profiles and fatigue in elite female and male team handball: individual and team characteristics - Wik, E. H. (2015)
Handball matches place diverse physical demands on players, which over the course of games may result in fatigue and decreased activity levels. However, studies are limited, and activity profiles are often obtained using video recordings, although this instrument may not be sensitive for capturing short-lasting handball-specific movements. The purpose of this master thesis is therefore to examine activity profiles and fatigue development, for teams and individual players of both genders, using modern microtechnology devices. A microtechnology device (Catapult OptimEye S5) was worn by elite players in a female national team (6 matches, n = 55 samples), and a male national recruit team (3 matches, n = 36 samples), during international tournament matches. Activity profiles were examined on a team- and individual player level, with special regards to possible fatigue development during games. Analyses were performed for Player Load™, accelerations, decelerations, and changes of direction (CoD), as well as high- and moderate-intensity efforts combined (HMI) and lowintensity efforts (LI), all relative to playing time.